2022
DOI: 10.1111/iwj.13875
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between different suture techniques in lumbar spine surgery

Abstract: As a result of solicited muscles, strong friction, and tensile force on cutaneous tissue, the difference in closure procedure and management strategies and complications of surgical incision healing is a real challenge in lumbar spine surgery. We performed a retrospective study to compare different types of wound closure in lumbar spine surgery. 4383 patients were included in this study. Wound dehiscence was more common in the intracutaneous suture group than in the far-near-near-far suture group. Delayed woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Super cial surgical site infections are a signi cant concern in spine surgery due to their potential sequelae [9,10]. This study aimed to address this concern by comparing the impact of two commonly used skin closure techniques, intracutaneous sutures and staple-assisted closure, on wound healing and infection rates in non-instrumented primary spine surgery [7,11]. Our study's main nding were i) the rate of infections was generally low in both cohorts and independent of the applied skin closure technique, and ii) closure with staples was the faster option which, however, did not signi cantly impact the total operating time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Super cial surgical site infections are a signi cant concern in spine surgery due to their potential sequelae [9,10]. This study aimed to address this concern by comparing the impact of two commonly used skin closure techniques, intracutaneous sutures and staple-assisted closure, on wound healing and infection rates in non-instrumented primary spine surgery [7,11]. Our study's main nding were i) the rate of infections was generally low in both cohorts and independent of the applied skin closure technique, and ii) closure with staples was the faster option which, however, did not signi cantly impact the total operating time.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the available literature concerning wound closure methods in spine surgery is mostly retrospective, monocentric and heterogeneous by including instrumented fusion procedures as well as revision surgeries [5][6][7]13]. For instance, a systematic review by Yilmaz et al on posterior spinal fusion revealed that sutures were associated with reduced wound infection rates compared to staples in six retrospective studies with potentially bene cial effects of Silverloin wound dressings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, our clips vs. suture model demonstrated an accuracy of >93% accuracy, and our temporal trend analysis showed a preference for using sutures for wound closure. Various studies have concluded that suturing is more efficient when compared with the use of clips for good wound closure, resulting in lower rates of separation, prevention of SSI, and ultimately shorter hospital LOS ( 41 , 42 ). Contrastingly, postoperative analysis of visual analogue pain scores comparing the use of clips to non-absorbable sutures have also demonstrated a significantly quicker and pain-free experience for patients with stapled wounds ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…El cierre de la herida quirúrgica es un procedimiento del cual depende en gran medida la adecuada resolución de la herida, el riesgo de ISQ, y la cicatrización 270,271 . Actualmente se dispone de diferentes técnicas y materiales que pueden ser empleados para tal fin, como suturas estándar, monofilamento, multifilamento, antibacterianas, barbadas o de púas, absorbibles, suturas continuas o intermitentes y grapas, entre otros [272][273][274] , los cuales varían en características tales como resistencia o flexibilidad cuando se pasa a través de los tejidos, extensión del daño tisular causado cuando se pasa a través de los tejidos, resistencia a la tracción o tensión de la herida, grado de reacción inflamatoria causada y probabilidad de formación de tejido fibroso 275 . Por lo anterior, es necesario conocer, de acuerdo con la mejor evidencia disponible que método de cierre de la herida incisional es efectivo en la prevención de la ISQ.…”
Section: Antecedentesunclassified